Human Empowerment: A Case Study of Tijāniyyah Grassroots Mobilization and Empowerment Initiative of Nigeria (TIGMEIN) Osun State, Nigeria (Journal of Management and Social Sciences, 2025)
Tijāniyyah is one of the groups in Sūfi Islamic order. Sufism or Tasawwuf, has its root in the early days of Islam, i.e., it is as old as Islam, but its transformation as a distinct movement occurred over time. Tijāniyyah Sufi order was founded by Ahmad al-Tijani (1735-1815). The name Tijaniyyah is derived from his name “Al-Tijani”, which refers to his birthplace, Tijani, a small village in Algeria. The order came to Nigeria at a very early stage, perhaps during the lifetime of its founder. The order has faced criticism and controversy from some scholars and groups, who accuse it of introducing innovations (bid’ah) in Islam. This paper aims to unveil its contributions and how its empowerment programme benefited the people of Osun State. It also unearths the roles and activities of the Tijāniyyah Grassroots Mobilization and Empowerment Initiative of Nigeria (TIGMEIN), Osun State. The research used analytical method as well as survey method to achieve its set objectives. Findings from the study show that the group (TIGMEIN) under the umbrella of the Osun State Tijāniyyah Sūfi order has organised different trainings across all local government areas of Osun State to secure jobs for teeming unemployed youth and alleviate poverty in the State. The work therefore recommends that members of the group put in more effort to sustain the programme and that government, as well as other organisations in the State and Nigeria at large, should also assist the programme.